Radio Broadcasting and Indonesian Nationalism: During the Last Decade of Dutch Colonialism. Issue 1 (2nd January 2022) - Darmanto,; Masduki,; Wiryawan, Hari
ABSTRACT: This paper discusses how radio during the last decade of Dutch colonial era had served as an agent of nationalism in Indonesia. This paper applies a literature study using a historical approach that focused on Soloche Radio Vereeniging (SRV) and the Eastern Radio network, which were operational from the 1930s to the 1940s. The results suggest that SRV and Eastern Radio network during the Dutch colonial period served as tools of cultural resistance against the domination of European culture. Radio broadcasting was an alternative form of cultural diplomacy that promoted the birth of Indonesia, which had become free from colonialism.